PERANCANGAN PENGUKURAN KENYAMAN KEPUASAN PELANGGAN DALAM BERBELANJA DI GUARDIAN BATAM - SAPRISUL; Sirait, Ganda (Computer Science and Industrial Engineering, 2022)
XYZ is a daily necessities retailer located in the Riau Islands. It is a company engaged in a retail business network engaged in the fulfilment of daily basic needs. This researcher took data as many as 72 respondents who are XYZ customers, then calculated IPA and CSI. Based on the results of the IPA, the highest value, which is Regarding XYZ, has an extra benefit poster to facilitate transactions with a TKI level of 103,986 and the smallest is Regarding staff who explain product functions and benefits to customers with 72.472% TKI. There are 7 statements in the IPA I quadrant, 5 statements in quadrant II and 3 statements in quadrant II and 4 statements in the IPA IV quadrant. Based on the results of the CSI, customer satisfaction is 74.942%, this number shows that consumers are satisfied with the services provided. Some of the services that are prioritized for improvement in quadrant 1 are Cleanliness and customer convenience in shopping at XYZ. Cleanliness of the gondola and product tidiness at XYZ, How XYZ employees serve customers according to customer expectations, Staff who explain product functions and benefits to customers, Regarding service to customers with uncomplicated, XYZ staff service quickly Spg is responsive in serving customers, and XYZ staff has the ability and knowledge so that they can find out customer needs and actions that must be given to customers